2018
DOI: 10.1007/s10555-018-9744-y
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 polyunsaturated fatty acids as adjuvant therapy of colorectal cancer

Abstract: The majority of evidence linking anti-colorectal cancer (CRC) activity with omega-3 polyunsaturated fatty acids (O3FAs) has focussed on decreased CRC risk (prevention). More recently, preclinical data and human observational studies have begun to make the case for adjuvant treatment of advanced CRC. Herein, we review latest data regarding the effect of O3FAs on post-diagnosis CRC outcomes, including mechanistic preclinical data, evidence that O3FAs have beneficial effects on efficacy and tolerability of CRC ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 88 publications
(100 reference statements)
1
63
0
3
Order By: Relevance
“…However, other authors found no link between n-3 and n-6 PUFAs and CRC development or treatment outcomes [9]. Furthermore, the available evidence in this matter is insufficient, as most preclinical studies analyzed the direct effects of selected n-3 PUFAs on cancer cells in vitro, rather than in vivo [10]. Some evidence suggests that potential therapeutic effects of n-3 PUFAs, if any, may depend on their dose, concomitant chemotherapy and its regimen [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, other authors found no link between n-3 and n-6 PUFAs and CRC development or treatment outcomes [9]. Furthermore, the available evidence in this matter is insufficient, as most preclinical studies analyzed the direct effects of selected n-3 PUFAs on cancer cells in vitro, rather than in vivo [10]. Some evidence suggests that potential therapeutic effects of n-3 PUFAs, if any, may depend on their dose, concomitant chemotherapy and its regimen [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the interaction between gut microbiota and the immune checkpoint pathway has been discovered [ 2 , 3 , 4 ], the mechanism of interaction needs to be elucidated. A strong, direct correlation was observed in several studies between n-3/n-6 PUFA levels and the microbiome [ 18 ], while an inverse correlation was observed for n-3 PUFA levels and inflammation [ 9 ]. Although several studies have demonstrated a direct link between n-3/n-6 levels and the microbiome and independently between n-3/n-6 levels with inflammation, the causal relationship whether n-3/n-6 levels modulate the interaction between the microbiome and the immune system has been circumstantial at best [ 18 , 19 , 20 ].…”
Section: Hypothesis: N-3 and N-6 Pufas Modulate The Microbiome Andmentioning
confidence: 99%
“…A strong, direct correlation was observed in several studies between n-3/n-6 PUFA levels and the microbiome [ 18 ], while an inverse correlation was observed for n-3 PUFA levels and inflammation [ 9 ]. Although several studies have demonstrated a direct link between n-3/n-6 levels and the microbiome and independently between n-3/n-6 levels with inflammation, the causal relationship whether n-3/n-6 levels modulate the interaction between the microbiome and the immune system has been circumstantial at best [ 18 , 19 , 20 ]. This communication hypothesises that higher n-3 PUFA and lower n-6 PUFA levels lower inflammation and promote the growth of favourable gut microbes.…”
Section: Hypothesis: N-3 and N-6 Pufas Modulate The Microbiome Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Mortality rates in LMICs were 2-fold higher for cervical cancer and 40% higher for male lung and liver cancers during . Omega-3s from fish pack a stronger punch than other oils when it comes to cancer prevention [113][114][115]. Seaweeds are specifically used to treat tumors in CHM [116].…”
Section: Introductionmentioning
confidence: 99%